Demographics and inflation - Elena Bobeica; Christiane Nickel; Eliza Lis; Yiqiao Sun (European Central Bank (ECB), 2017)
Most euro area countries have entered an unprecedented ageing process: life expectancy continues to rise and fertility rates have declined, while retirement age in the last twenty to thirty years hardly increased. This implies an ever smaller fraction of the working age population in total population, leading to changes in consumption and saving behaviours and having an important impact on the macroeconomy. In this paper we focus on the relationship between demographic change and inflation. We find that based on a cointegrated VAR model there is a positive long-run relationship between inflation and the growth rate of working-age population as a share in total population in the euro area countries as a whole, but also in the US and Germany. We also find that this relation is mitigated by the effect of monetary policy, which we account for by including the short-term interest rate in our analysis. One caveat of the analysis could be that the empirical relationship as found does not sufficiently take into account changes in policy settings following the high inflation experiences in the 1970s. Our findings support the view that demographic trends are among the forces that shape the economic environment in which monetary policy operates. This is particularly relevant for countries, like many in Europe, that face an ageing process.
Keywords: E31; J11; C22; 330; cointegration; demographic change; inflation